Analysis of Wood Powder Product Defects Using Six Sigma DMAIC and Failure Mode Effect Analysis Methods - Wildan Dwi Fhahillal; Elly Ismiyah (JTI: Jurnal Teknik Industri, 2025)
CV. XYZ is a supplier of waste wood powder, specifically utilizing Merbau wood. The company currently faces product quality issues, including powder mixed with other sizes (43.2%), foul odor and mold (16.2%), and excessive moisture/wetness (40.6%). This study aims to analyze and improve product quality using Six Sigma and FMEA methods. The results indicate an average DPMO value of 40,621 with a Sigma level of 2.46, suggesting that the process is not yet optimal. The FMEA analysis identified the machine factor as the primary cause of defects, with the highest Risk Priority Number (RPN) of 540. Improvement recommendations include machine recalibration, scheduled cleaning, and preventive maintenance. The implementation of these strategies is expected to reduce defects and enhance the company's competitiveness. This research contributes to quality control in the wood powder waste processing industry and opens opportunities for further research into developing more effective systems. Keywords: Defects, Six Sigma, DMAIC, FMEA, Quality Control, Product Defects